2009
DOI: 10.1002/pros.21017
|View full text |Cite
|
Sign up to set email alerts
|

Genistein and resveratrol, alone and in combination, suppress prostate cancer in SV‐40 tag rats

Abstract: Background Chemoprevention utilizing dietary agents is an effective means to slow the development of prostate cancer. We evaluated the potential additive and synergistic effects of genistein and resveratrol for suppressing prostate cancer in the Simian Virus-40 T-antigen (SV-40 Tag) targeted probasin promoter rat model, a transgenic model of spontaneously developing prostate cancer. Methods Rats were fed genistein or resveratrol (250 mg/kg AIN-76A diet) alone and in combination, and a low dose combination (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 36 publications
3
62
1
Order By: Relevance
“…Because androgen-dependent AR function plays a pivotal role in the development of prostate cancer, AR is recognized as a preventative and therapeutic target for prostate cancer [9]. Resveratrol inhibits the prostate cancer cells in vitro and suppresses the progression of prostate cancer in in vivo mouse and rat adenocarcinoma models [12,16,27,28]. In the present study, we identified the mechanism by which resveratrol inhibits the transcriptional activity of AR.…”
Section: Discussionmentioning
confidence: 78%
“…Because androgen-dependent AR function plays a pivotal role in the development of prostate cancer, AR is recognized as a preventative and therapeutic target for prostate cancer [9]. Resveratrol inhibits the prostate cancer cells in vitro and suppresses the progression of prostate cancer in in vivo mouse and rat adenocarcinoma models [12,16,27,28]. In the present study, we identified the mechanism by which resveratrol inhibits the transcriptional activity of AR.…”
Section: Discussionmentioning
confidence: 78%
“…Resveratrol, a stilbene found in grapes, has been shown to inhibit a variety of primary tumors. [5][6][7][8][9] Pterostilbene, an analogue of resveratrol found in blueberries, has been shown to inhibit gastric, colon, and breast cancer as well as leukemia and melanoma in various in vitro and animal model systems. [10][11][12][13][14][15] Furthermore, its molecular structure makes it substantially more bioavailable than resveratrol upon oral ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…A high SRC-3 protein level also correlates with resistance to EGFR antagonists in lung cancers (Cai et al 2010). On the other hand, downregulation of the SRC-3 protein level is considered an important step for enhancing the ability of several anticancer agents to effectively combat cancers (Harper et al 2009;Li et al 2009a,b). Thus, the expression level of SRC-3 may be an important factor in controlling the responses of cancer cells to anti-cancer therapies.…”
mentioning
confidence: 99%